How Does Status Affect Performance? Status as an Asset vs. Status as a Liability in the PGA and NASCAR - Bothner, Matthew S.; Kim, Young-Kyu; Smith, Edward Bishop (Organization Science, 2012)
Two competing predictions about the effect of status on performance appear in the organizational theory and sociological literatures. On one hand, various researchers have asserted that status improves performance. This line of work emphasizes tangible and intangible resources that accrue to occupants of high-status positions and therefore pictures status as an asset. On the other hand, a second stream of research argues that status instead diminishes performance. This alternative line of work emphasizes complacency and distraction as deleterious processes that plague occupants of high-status positions and thus portrays status as a liability. Which of these two perspectives best characterizes the actual performance of individuals in a competitive setting? And are they in any way reconcilable? In this paper, we summarize these two perspectives and test them in two empirical settings: the Professional Golf Association (PGA) and the National Association for Stock Car Auto Racing (NASCAR). Using panel data on the PGA Tour, we model golfers' strokes from par in each competition as a function of their status in the sport. Using similar data on NASCAR's Winston Cup Series, we model drivers' speed in the qualifying round as a function of their status in the sport. We find curvilinear effects of status in both contexts. Performance improves with status until a very high level of status is reached, after which performance wanes. This result not only concurs with the view that status brings tangible and intangible resources but also provides empirical support for the contention that status fosters dispositions and behaviors that ultimately erode performance.